Optimalisasi Penggunaan Image Stitching dan Seam Carving dalam Pengembangan Tur Virtual Responsif - Buana, Pratama Angga; Putri, Astrid Novita; Adinugroho, Suryo (Building of Informatics, Technology and Science (BITS), 2024)
Nglurah Village, Tawangmangu, still faces challenges in effective tourism promotion due to the use of conventional promotional methods. This study employs a mixed-method approach to identify the issues and expectations of tourism managers. The results indicate that 50% of managers struggle with tourism promotion, and 70% believe that the implementation of technology is crucial to promote the village's tourism potential in an attractive and interactive way. This research aims to combine image stitching and seam carving methods to enhance the quality and diversity of responsive virtual tour applications. Image stitching is the process of merging multiple 360° panoramic images into a single comprehensive image that accurately represents the actual scene. Meanwhile, seam carving is a technique for carefully cropping an image to remove less important parts while preserving important areas when the image is resized. The collaboration of these two methods is expected to produce virtual tour applications that can adapt to the shape and size of gadgets without losing important content. This virtual tour application is expected to enhance the user experience in virtual tourism and open up opportunities for technology-based tourism development in Tawangmangu Village. Additionally, this research can increase the attractiveness of Tawangmangu Village tourism and provide a foundation for further research in virtual tour development.